2019
DOI: 10.1089/chi.2018.0225
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences in Infancy and Toddlerhood Predict Obesity and Health Outcomes in Middle Childhood

Abstract: Background: The Adverse Childhood Experiences (ACEs) study articulated the negative effects of childhood trauma on adult weight and health. The purpose of the current study is to examine the associations between ACEs in infancy and toddlerhood and obesity and related health indicators in middle childhood. Methods: We used data collected from a sample of low-income families enrolled in the national evaluation of Early Head Start (EHS). Data come from 1335 demographically diverse families collected at or near ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 88 publications
0
50
0
Order By: Relevance
“…There are several possible explanations for this result: one may be that increases in overweight measures in response to stressful life events do not appear to occur instantaneously [ 13 ]. Previous research has found an association between the exposure to four or more ACEs and clinical obesity (95th percentile) [ 21 , 22 , 23 ]. Nevertheless, these traumatic events are a different type of event than PSEs, and their longer-term impact could be greater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several possible explanations for this result: one may be that increases in overweight measures in response to stressful life events do not appear to occur instantaneously [ 13 ]. Previous research has found an association between the exposure to four or more ACEs and clinical obesity (95th percentile) [ 21 , 22 , 23 ]. Nevertheless, these traumatic events are a different type of event than PSEs, and their longer-term impact could be greater.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, previous research has shown that presenting ≥ 4 ACE had a significant impact on the medical and psychological health status in adults, as well as in early and middle childhood. In paediatric samples, exposure to four or more ACE categories was associated with clinical obesity (Body Mass Index BMI ≥ 95th percentile) [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the intervening years, a range of studies confirmed and extended the evidence of negative physical and psychological consequences [10]. Combined, these studies document that experiencing even one adversity increases the risk of negative outcomes [11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 90%
“…Alarmingly, nearly half of children have experienced at least one ACE 11–14 . ACEs exposure has been associated with cardiovascular disease, cancer, and other poor health outcomes in adulthood 10,15–21 . ACEs' effect on the development of obesity has been studied much less than obesity risk factors related to individual health behavior.…”
Section: Introductionmentioning
confidence: 99%